Implementasi Nilai-Nilai Demokrasi Pada Mata Pelajaran PPKN Dengan Menggunakan Metode Inquiri Pada Kelas 8 (VIII) di SMPN 19 Malang - Rofina Odilia Mbere; Didik Iswahyudi; Romadhon Romadhon (International Forum of Researchers and Lecturers, 2023)
This research aims to find out what democratic values ​​are implemented in PPKn subjects at SMPN 19 Malang, the factors inhibiting the implementation of democratic values ​​at SMPN 19 Malang, and how democratic values ​​are implemented in PPKn subjects using the inquiry method at SMPN 19 Malang. This research uses a qualitative approach with a descriptive qualitative research type. The data collection techniques used were observation, interviews and documentation. The analysis technique uses triangulation techniques to obtain validity of the data, while the data analysis used in this research is reduction, display and verification. The research results show that, 1) Democratic values ​​have been implemented for a long time and are running well at SMPN 19 Malang. These values ​​consist of: tolerance, cooperation, responsibility, and deliberation to reach consensus. 2) Factors inhibiting implementation are students who violate school regulations and the existence of active and inactive student groups. 3) The implementation of democratic values ​​in PPKn subjects using the inquiry method at SMPN 19 Malang has apparently not been implemented by PPKn teachers. Because students are not yet able to study independently, students lack confidence and are embarrassed when asked to present in front of the class, as well as limited time in teaching and learning activities which means Civics teachers have not implemented learning using the inquiry method.